Analytical Method Development and Validation of RP-HPLC Method For Estimation of Empagliflozin in Bulk and Pharmaceutical Dosage Form - Madure, Vaishnavi; Barge, Vijaya (Journal of Neonatal Surgery, 2025)
In this study, researchers aimed to develop and validate a reproducible and precise Reverse Phase High-Performance Liquid Chromatography technique for accurately estimating a chemical related to empagliflozin. The primary objective was to establish a method suitable for quality control of empagliflozin batches and its impurities. To achieve this, effective chromatographic separation has done by using two mobile phases: The mixture of 0.1 % Trifluoroacetic acid in Water and Methanol with flow rate 1.2 ml/min. The chromatographic separation was done by using a Phenomenex C-18, 250 mm X 4.6 mm, 5 µm. The results indicated successful chromatographic separation and accurate quantification. The proposed method demonstrated its efficacy for quality monitoring of bulk samples containing Empagliflozin, ensuring the reliability and consistency necessary for routine quality control purposes in the pharmaceutical industry